Properties of TiO2 films deposited on flexible substrates using direct current magnetron sputtering and using high power impulse magnetron sputtering. (July 2015) - Twu, M.J.; Chiou, A.H.; Hu, C.C.; Hsu, C.Y.; Kuo, C.G.
Abstract: Mixture phases of anatase and rutile, TiO2 thin films are deposited on flexible polyethylene terephthalate (PET) substrates by direct current magnetron sputtering (dcMS) and high power impulse magnetron sputtering (HiPIMS), using a ceramic TiO2 target in an argon gas environment, at temperatures ranging from room to 150 °C. The Taguchi method for the design of a robust experiment, with an orthogonal array, a signal-to-noise ratio and an analysis of variance are used to analyze the performance characteristics of the deposition parameters. This study determines the effect of the deposition parameters, such as the dc power (W), the sputtering pressure (Pa) and the substrate temperature (°C) on the structural and photocatalytic characteristics of the TiO2 films. For both dcMS- and HiPIMS-grown films, the (110), (200) and (210) peaks of the rutile structure and the (200) peak of the anatase structure are observed. Compared to the coatings onto PET substrates using dcMS, the samples deposited using HiPIMS exhibited excellent photoinduced hydrophilicity and high photocatalytic activity. The contact angles are decreased to less than 4.1° after UV irradiation for 9 min, and the absorbance of the methylene blue aqueous solution is reduced to 0.3 for 240 min UV irradiation. Furthermore, the XRD diffraction peaks of the TiO2 films using HiPIMS become sharper and more intense, which demonstrates that the crystalline structure of the TiO2 films is improved. Higher visible-light photocatalytic efficiency was achieved with HiPIMS technique.